THE ESSENCE AND TYPES OF COMPETITIVE STRATEGIES - L. Kazbekova; K. Utegenova; A. Akhmetova; Z. Korzhynbayeva (Academic Journal of Physical and Chemical Sciences, 2019)
The article defines the essence of the competitive strategies of firms on the basis of a retrospective analysis of the theory of competitive strategies development. As a starting point of the study, the author uses the work by M. Porter, the founder of the theory of competitive strategies. Without diminishing the high importance of his theory of competitive strategies, the author notes the absence in his works of a clear and comprehensive definition of the concept of competitive strategy and carries out a further search in the works of other scientists who have made a definite contribution to the development of the theoretical basis of this direction. Analysis of existing theoretical developments on this topic allowed the author to formulate an author’s interpretation of the concept of "competitive strategies" and highlight the main features of competitive strategies. In addition, the concepts of "competitive actions" and "competition strategies" are distinguished in the work. The study of various scientific points of view and the evolution of diverse approaches to the classification of types of competitive strategies made it possible to develop the author’s classification according to a new classification criterion - according to the level of competitive activity of a business entity with the identification of their types. According to the author, the classification of types of competitive strategies that he forms systematizes the existing competitive strategies in the scientific literature by combining them into three large blocks, and is also the most suitable for use in the practical activities of industrial enterprises.